Synthesis of 1,3-diazaadamantanes containing a pyridine ring and study of their antioxidant properties - Gevorkyan, K. A.; Galstyan, M. V.; Buniatyan, J. M.; Muradyan, R. E.; Harutyunyan, A. D. («Գիտություն» հրատ.)
In search of new biologically active compounds among 1,3-diazaadamantanes, we previously synthesized new compounds containing indole, isatin, quinoline, and pyrazole derivatives in the 2-nd position of the adamantane ring. Biological studies of the synthesized compounds were carried out. Among them were compounds with antioxidant activity [1-3].In medical practice, drugs containing a pyridine ring are widely used: Tubazid, Ftavazide, Nicotine, Cordiamin [4]. 9-Հիդրօքսի-, 9-օքսո-, 9-մեթիլեն-1,5-(դիալկիլ-, մեթիլ-, ֆենիլ-, դիֆենիլ)-3,7-դիազաբիցիկլո/3.3.1/նոնանների և օ-, մ-, պ – պիրիդին ալդեհիդների կոն-դենսացմամբ սինթեզվել է 2-պիրիդիլ տեղակալված 1,3-դիազաադամանտան-ների նոր շարք: Ստացված միացությունների հակաօքսիդանտային հատկու-թյունների ուսումնասիրությունը ցույց է տվել որ, որոշ միացություններ 10-3 կոնցենտրացիայում ցուցաբերում են միջին և թույլ արտահայտված հակաօքսի-դանտային ակտիվություն: Конденсацией 9-гидрокси-, 9-оксо-, 9-метилен-1,5-(диалкил-, метилфенил-, дифенил)-3,7-диазабицикло/3.3.1/нонанов с о-, м-, п- пиридилальдегидами синтезирован новый ряд 2-замещенных-1,3-диазаадамантанов. Изучением антибак-териальной активности синтезированных соединений установлено, что некоторые соединения этого ряда в концентрации 10-3 проявляют средную и слабую активность.
Keywords: Organic and Bioorganic Chemistry